The heavy LIFT: An approach to retention for HBCUs. Issue 195 (5th May 2022) - Lyn, Jamila S.; Winfield, James K.
Abstract: In campus environments where resources are low and demand for student and institutional success are high, there is an increased need to build a collaborative network and team aimed at advancing advising practices that promote retention, persistence, and navigation of resources for students. This chapter illustrates the use of a team‐based approach, known as the LIFT framework, at Benedict College, a small private HBCU in Columbia, South Carolina. This framework allowed the institution to leverage campus resources, innovate the faculty advising model in collaboration with practices from a centralized Student Success Center, focus on barriers to campus resource navigation, and tailor best practices to institutional needs and priorities. The LIFT framework is not only important to HBCUs but also transferable to any institutions that want to center the needs of underserved students.